INTERPRETATION OF CULTURAL REALITIES IN LITERARY TRANSLATION IN ENGLISH AND UZBEK (Eureka Journal of Language, Culture & Social Change, 2026)
This study investigates the linguistic and extra-linguistic challenges of translating cultural realities (realia) between English and Uzbek, two typologically and culturally distant languages. Using an asymmetric comparative framework, the paper analyzes the efficiency of various translation strategies such as calque, transliteration, adaptation, and descriptive translation in maintaining the conceptual equivalence of source texts. The results indicate that while direct borrowing preserves foreign flavoring, it frequently induces cognitive dissonance in the target audience due to a lack of shared historical context. Conversely, functional equivalence maintains readability at the cost of cultural dilution. The study proposes a hybrid pragmatic translation model aimed at optimizing cross-cultural decoding in Uzbek-English literary translation.
Keywords: Literary translation, cultural realities, realia, zero-equivalence, foreignization, domestication, English-Uzbek translation, pragmatic equivalence, cultural untranslatability, comparative linguistics.